Reducing The Cost of Transport and Increasing Walking Distance After Stroke: A Randomized Controlled Trial on Fast Locomotor Training Combined With Functional Electrical Stimulation. (August 2016) - Awad, Louis N.; Reisman, Darcy S.; Pohlig, Ryan T.; Binder-Macleod, Stuart A.
Background . Neurorehabilitation efforts have been limited in their ability to restore walking function after stroke. Recent work has demonstrated proof-of-concept for a functional electrical stimulation (FES)–based combination therapy designed to improve poststroke walking by targeting deficits in paretic propulsion. Objectives . To determine the effects on the energy cost of walking (EC) and long-distance walking ability of locomotor training that combines fast walking with FES to the paretic ankle musculature (FastFES). Methods . Fifty participants >6 months poststroke were randomized to 12 weeks of gait training at self-selected speeds (SS), fast speeds (Fast), or FastFES. Participants' 6-minute walk test (6MWT) distance and EC at comfortable (EC-CWS) and fast (EC-Fast) walking speeds were measured pretraining, posttraining, and at a 3-month follow-up. A reduction in EC-CWS, independent of changes in speed, was the primary outcome. Group differences in the number of 6MWT responders and moderation by baseline speed were also evaluated. Results . When compared with SS and Fast, FastFES produced larger reductions in EC ( P s ≤.03). FastFES produced reductions of 24% and 19% in EC-CWS and EC-Fast ( P s <.001), respectively, whereas neither Fast nor SS influenced EC. Between-group 6MWT differences were not observed; however, 73% of FastFES and 68% of Fast participants were responders, in contrast to 35% of SS participants. Conclusions . Combining fast locomotor training with FES is an effective approach to reducing the high EC of persons poststroke. Surprisingly, differences in 6MWT gains were not observed between groups. Closer inspection of the 6MWT and EC relationship and elucidation of how reduced EC may influence walking-related disability is warranted.